Carrier aircraft, 1917-present - Newdick, Thomas (The essential aircraft identification guide, 2011)
" ... Organized by era and contry of origin, the book offers a comprehensive survey of naval planes and helicopters, including examples produced by the US, Russia, Japan, Sweden, the UK and France. Separate sections detail the aircraft by campaign, such as Japanese aircraft in the Pacific theatre (1941-45), Argentina in the Cold War era, France from 1946-[60] and modern US aircraft, 1990 to the present day. [The book] includes every major carrier-launched type, from fighters, ground-attack, torpedo bombers and reconnaissance aircraft to search-and-rescue helicopters. ..."